Family caregivers' distress responses to daily behavioral and psychological symptoms of dementia: The moderating role of relationship quality. (11th December 2020) - Chunga, Richard E.; Kim, Kyungmin; Liu, Yin; Zarit, Steven H.
Abstract: Objectives: Behavioral and psychological symptoms of dementia (BPSD) are associated with distress among caregivers of persons with dementia (PWD), but less is known about how relationship quality may buffer this association. This study examines the association between daily BPSD and daily perceived distress among family caregivers and the moderating role of relationship quality. Methods: Data were from 173 family caregivers of PWD from the Daily Stress and Health study. Relationship quality was assessed at the baseline interview; then on each of the 8 following consecutive days, caregivers reported frequency of daily BPSD (six domains) and their respective distress (calculated as daily distress sum and daily distress mean scores) through daily evening phone interviews at home. A 2‐level multilevel model approach was employed to differentiate within‐person (WP) and between‐person (BP) effects. Results: Greater daily BPSD occurrence was associated with higher daily distress ( sum and mean scores) at WP and BP levels. However, relationship quality moderated the association between daily BPSD occurrence and daily distress sum scores at both WP and BP levels. Caregivers who reported better relationship quality with the PWD had lower levels of daily distress sum scores in response to daily BPSD occurrence, compared to their counterparts with poorer relationship quality. Conclusions: This study revealed that relationship quality attenuated the effect of daily BPSD occurrence on caregivers' distress. Future dementia caregiver education and support programs should consider building relationship quality into the personalized program design to improve caregiver mental health and well‐being.